Peripersonal Space as the space of the Bodily Self - Noel, Jean-Paul (Cognition, 2015)
Bodily self-consciousness (BSC) refers to experience of our self as located within an owned body (self-identification) and as occupying a specific location in space (self-location). BSC can be altered through multisensory stimulation, as in the Full Body Illusion (FBI). If participants view a virtual body from a distance being stroked, while receiving synchronous tactile stroking on their physical body, they feel such as the virtual body were their own and they experience, subjectively, to drift toward the virtual body. Here we hypothesized that - while normally the experience of the body in space depends on the integration of multisensory body-related signals within a limited space surrounding the body (i.e. peripersonal space, PPS) - during the FBI the boundaries of PPS would shift toward the virtual body, that is toward the position of self-location. To test this hypothesis, we used synchronous visuo-tactile stroking to induce the FBI, as contrasted with a control condition of asynchronous stroking. Concurrently, we applied an audio-tactile interaction paradigm to estimate the boundaries of PPS. PPS was measured in front of and behind the participants' body as the distance where tactile information interacted with auditory stimuli looming in space toward the participant's physical body. We found that during synchronous stroking, i.e. when participants experienced the FBI, PPS boundaries extended in the front-space, toward the avatar, and concurrently shrunk in the back-space, as compared to the asynchronous stroking control condition, where no FBI was induced. These findings support the view that during the FBI, PPS boundaries translate toward the virtual body, such that the PPS representation shifts from being centered at the location of the physical body to being now centered at the subjectively experienced location of the self.